Clinical comparison of single-incision and dual-incision approaches for the treatment of distal tibial and fibular fractures: A randomized controlled trial. (12th June 2020) - An, Lin; Zhang, Jingwei; Ma, Weihu; Zhu, Limei; He, Xianfeng; Ying, Jichong; Zhuang, Yunqiang; Zhuang, Yunqiang; Yu, Tianming
Purpose: The purpose of this study was to clinically compare the single-incision and dual-incision approaches for the treatment of distal tibial and fibular fractures. Methods: In total, 93 patients were enrolled, and the mean follow-up was 15 months (range 12–19 months). The patients treated for open reduction and internal fixation were randomly classified into two groups based on the approach used: 45 patients were treated using the single-incision approach (group 1) and 48 patients were treated using the dual-incision approach (group 2). In these two groups, operation time, discharge time, postoperative complications, and ankle function evaluations (Olerud–Molander Ankle Score) were compared between the two groups. Results: There were no significant differences in the mean operation time (98.2 ± 18.5 vs. 103.6 ± 19.3), discharge time (11.1 ± 3.9 vs. 12.5 ± 5.7), overall surgical complication rates (9/45 vs. 15/48), or ankle function between the two groups ( p > 0.05). However, the rate of soft tissue-related complications, such as skin slough, infection, nonunion, and delayed union, was significantly lower in group 1 (5/45) than in group 2 (14/48) ( p < 0.05). Conclusion: The two incision approaches were found to have similar clinical outcomes. However, with regard to soft tissue conservation, the single-incision approach was superior to the dual-incision and maybe a reliable alternative.